Pengaruh Kualitas Pelayanan Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Pada Bara Bara Shoes Malang - Azzam Riski; Muhammad Ridwan Basalamah; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Problems in customer finance arise when one of the factors is not met, such as the quality of service obtained is very bad, the price does not match the goods sold, and the poor quality of the products offered, and the most important factor itself in customer satisfaction is the quality of service to customer satisfaction. The second factor affecting customer satisfaction is product quality, and the third factor is price, price is determined by the balance between supply and demand for service quality to customer decisions. This study aims to prove whether there is influence of service quality, product quality and price on purchasing decisions at the bara-bara shoes store. The sampling technique used purposive sampling method, with a total sample of 85 respondents. Data analysis used multiple regression analysis which was processed using SPSS 23 software. Data collection techniques used questionnaires. The results showed (1) there was an effect of service quality, product quality and price on purchasing decisions, with a Fcount value of 6,905 > Ftable 2.71, a significance value of 0.000 <0.05, and R Square 0,874 (67.4%) (2) there was an effect of service quality on customer decisions, with a tcount value of 3,665 > ttable 1,989 and a significance value of t 0.000 <0.05 (3) there was an influence product quality on purchasing decisions, with a t-count of 2,111 > t-table of 1.989 and a significance value of 0.047 <0.05 (4) there is an effect of price on purchasing decisions, with a t-count of 7,059 > t-table of 1.989 and a significance value of 0.000 <0.05 Keywords: Service Quality, Product Quality, Price, Purchase Decision.